Twitter Sentiment Analysis on Credit Card - Syahdatul Maulida; Aam Slamet Rusydiana (Maqasid al-Shariah Review, 2022)
This research aims to evaluate the public's response to the global development of credit cards using primary data from Twitter tweets between January 1, 2019, and March 28, 2023. The research method employed is a qualitative approach using Python Library software called VADER (Valence Aware Dictionary and Sentiment Reasoner) to classify sentiments in these tweets. The research results indicate that the majority of the public has a neutral sentiment, accounting for approximately 97.6% towards credit cards, while positive sentiment reaches 1.7%, and negative sentiment is approximately 0.7%. Some keywords frequently appearing in the tweets include credit card, card needed, ASTRA Coins, card debt, and mobile users. It is expected that this research on public sentiment can assist relevant stakeholders in taking appropriate steps to enhance credit card usage and increase awareness and support for it. We also analyze the shariah perspective on credit card.